PEMANFAATAN LITERASI DIGITAL KEAGAMAAN DALAM MENUMBUHKAN SIKAP MODERASI BERAGAMA SISWA - Agusta, Erna Sari (LPMP Provinsi DKI Jakarta, 2024)
Digital spaces are often a source of religious learning for students. This phenomenon has positive and negative impacts. Digitalization makes it easier to obtain religious content quickly and widely. However, the rise of hoax content and hate speech in content can result in eroding students' religious moderation attitudes. This research was conducted using a quantitative approach through survey methods to quantitatively describe digital literacy tendencies and attitudes of religious moderation. The case study was conducted on MTsN 28 Jakarta students. The research results found that students' religious digital literacy was in the good category. Students master ICT skills, think creatively and imaginatively, participate in digital spaces, communicate through digital technology media, search and select information, think critically in contributing and analyzing, in line with social and cultural contexts, and ensure security when exploring information, creating, and collaborating with digital technology. Students' religious moderation attitudes are also in the very good category. Students have very good attitudes of national commitment, tolerance, non-violence and accommodating towards culture. Thus, it can be said that religious digital literacy has an impact on students' religious moderation attitudes. Therefore, it is necessary to strengthen religious literacy programs in educational institutions through digital media to strengthen students' religious moderation attitudes.